2018
DOI: 10.3345/kjp.2017.06100
|View full text |Cite
|
Sign up to set email alerts
|

The changes of prevalence and etiology of pediatric pneumonia from National Emergency Department Information System in Korea, between 2007 and 2014

Abstract: PurposeUnderstanding changes in pathogen and pneumonia prevalence among pediatric pneumonia patients is important for the prevention of infectious diseases.MethodsWe retrospectively analyzed data of children younger than 18 years diagnosed with pneumonia at 117 Emergency Departments in Korea between 2007 and 2014.ResultsOver the study period, 329,380 pediatric cases of pneumonia were identified. The most frequent age group was 1–3 years old (48.6%) and the next was less than 12 months of age (17.4%). Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…A comprehension of these dependencies may ameliorate the use of antimicrobials and the clinical approach in everyday practice. Viral/possibly viral etiology was found in 17.9% of cases in our study; these results are in line with a Taiwanese study, in which viral pneumonia accounted for 17.4% of pneumonia cases [ 11 ], while other researchers have report varied data, ranging from 8.4% in a Korean study to 70.4% in data from Ecuador [ 12 , 14 ]. Nevertheless, some generalizations may be made.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A comprehension of these dependencies may ameliorate the use of antimicrobials and the clinical approach in everyday practice. Viral/possibly viral etiology was found in 17.9% of cases in our study; these results are in line with a Taiwanese study, in which viral pneumonia accounted for 17.4% of pneumonia cases [ 11 ], while other researchers have report varied data, ranging from 8.4% in a Korean study to 70.4% in data from Ecuador [ 12 , 14 ]. Nevertheless, some generalizations may be made.…”
Section: Discussionsupporting
confidence: 92%
“…Prior to the introduction of conjugate vaccines, typical bacteria, i.e., Streptococcus pneumoniae ( S. pneumoniae ) and Hemophilus influenzae type B, were the most common causes of pneumonia [ 8 ], yet pediatric vaccination programs managed to decrease its frequency, and more cases of viral pneumonia are now diagnosed; a recent development in diagnostic techniques has also played an important role [ 10 ]. Viral etiology is most commonly related with respiratory syncytial virus (RSV), influenza, and adenovirus [ 11 , 12 , 13 , 14 , 15 , 16 ], and strongly relies on virus detection in upper respiratory tract samples; thus, the risk of a false-positive result related to colonization instead of an infection may be encountered [ 10 ]. On the other hand, blood cultures pose the risk of a false-negative outcome, since a positive result is seen only in 2.5–15% of samples [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the importance of MP as a pathogen causing bronchiolitis. MP was reported as an important pathogen in children with community-acquired pneumonia [ 13 , 14 ]. Two studies from Guangzhou and Suzhou in southern China reported that the rate of MP infection was 11.3% and 36.08%, respectively [ 14 , 15 ], and another study in 5 cities of southern and northern China reported that the rate of MP infection was 25.5% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma pneumoniae (MP) is a common cause of upper and lower respiratory tract disease in both children and adults. In the post-pneumococcal conjugate vaccine (PCV) 13 era, MP has become the leading cause of pediatric community-acquired pneumonia (CAP) in countries where PCV13 is included in the national immunization program [ 1 , 2 ]. Clinical symptoms are usually mild, although occasionally MP infection can be life-threatening as it can cause extra-respiratory manifestations, mainly skin lesions, hematologic disorders, and cardiovascular and nervous disease [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%